Estrategia de gestión de activos 4.0 para equipos rotativos en Mexichem resinas Colombia (2023)
Maintenance and Reliability practices, including health control, are largely governed by the type of resource being maintained and the associated failure patterns of those resources. To control the state of assets in the industry it is necessary to follow steps such as observation, research, resolution of identified conflicts and documentation of the process. This can generate or demand a large amount of time if you do not have technological tools that can optimize time with the development of repetitive tasks, therefore, and in evidence of the amount of rotating equipment of the company Mexichem Resinas de Colombia, so it was proposed the development of the project that had the purpose of proposing to the company an asset management technology 4.0 that satisfies the need for 24/7/365 real-time management and monitoring of the rotating equipment operating in the plant.